3d virtual modelling of existing objects by terrestrial photogrammetric methods - case study of barutana - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2017)
Three dimensional virtual modelling of existing objects (buildings or structures) is applicable in various fields of science and practice: architecture, civil engineering, urbanism, geology, mechanical engineering, video games and movie industry, medicine, archeology, safety of people and goods, etc. Photogrammetry, as a method of obtaining data of three-dimensional spatial structures based on two-dimensional images, is used, thanks to a number of software packages, for creating 3D models of objects and other spatial structures. This study analyses terrestrial semiautomatic and automatic photogrammetric methods, both presented through process of creating 3D model of an old existing historical building - Barutana (military gun powder warehouse), built in Ottoman empire, located in the fortress of the city of Nis in Serbia. The aim of the paper is comparison of two photogrammetric methods - semiautomatic and automatic in accuracy and efficiency through case study of Barutana.
Keywords: automatic photogrammetry; Barutana; existing objects; semiautomatic photogrammetry; virtual 3D models; DOCUMENTATION; INFORMATION; RECONSTRUCTION; EXTRACTION; LASER